Bioprinting in cardiovascular tissue engineering: a review - Lee, Jia Min (2018)
Fabrication techniques for cardiac tissue engineering have been evolving around scaffold-based and scaffold-free approaches. Conventional fabrication approaches lack control over scalability and homogeneous cell distribution. Bioprinting provides a technological platform for controlled deposition of biomaterials, cells, and biological factors in an organized fashion. Bioprinting is capable of alternating heterogeneous cell printing, printing anatomical relevant structure and microchannels resembling vasculature network. These are essential features of an engineered cardiac tissue. Bioprinting can potentially build engineered cardiac construct that resembles native tissue across macro to nanoscale.